Uji Daya Hambat Ekstrak Etanol dan N-Heksana Daun Labu Kuning (Cucurbita moschata D.) terhadap Bakteri Staphylococcus epidermidis - Herlinda Mawardika; Lia Agustina; Ovie Resta Vanesha (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Pumpkin leaf plant (Cucurbita moschata D.) is commonly used to treat gastric pain, jaundice, hipercholesterol, and contains antibacterial compounds. Nature products derived from plants are often used to treat facial skin disease by inhibiting acne-causing bacteria. Staphylococcus epidermidis has important role in acne formation. This research aims to determine the antibacterial activity, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) of 70% ethanol extract and n-hexane against Staphylococcus epidermidis. Pumpkin leaf extracts were obtained by maceration technique then diluted to obtain the extracts with concentrations of 10%, 25%, and 50%. The antibacterial activity test of pumpkin leaves was carried out in vitro by well diffusion method on Mueller Hinton Agar (MHA) media, while MIC and MBC was determined by dilution method using different concentration of extract. The results of this research showed that there was inhibition zone formed at concentration 10%, 25%, and 50% of 70% ethanol extract of yellow pumpkin leaves. According to the result, the largest inhibition zone was obtained at concentration of 50% (20.02 ± 0,28 mm). The MIC value was found at concentration of 12.5% and MBC value was determined at 50% concentration of ethanol extract. Meanwhile, n-hexane extract of yellow pumpkin leaves has no antibacterial activity against S. epidermidis. It can be concluded that ethanol extract of yellow pumpkin leaves has potent antibiotic material for S. epidermidis.